On cloud ice induced absorption and polarisation effects in microwave limb sounding - P. Eriksson; B. Rydberg; S. A. Buehler (Atmospheric Measurement Techniques, 2011)
Microwave limb sounding in the presence of ice clouds was studied by detailed simulations, where clouds and other atmospheric variables varied in three dimensions and the full polarisation state was considered. Scattering particles were assumed to be horizontally aligned oblate spheroids with a size distribution parameterized in terms of temperature and ice water content. A general finding was that particle absorption is significant for limb sounding, which is in contrast to the down-looking case, where it is usually insignificant. Another general finding was that single scattering can be assumed for cloud optical paths below about 0.1, which is thus an important threshold with respect to the complexity and accuracy of retrieval algorithms. The representation of particle sizes during the retrieval is also discussed. Concerning polarisation, specific findings were as follows: Firstly, no significant degree of circular polarisation was found for the considered particle type. Secondly, for the ±45° polarisation components, differences of up to 4 K in brightness temperature were found, but differences were much smaller when single scattering conditions applied. Thirdly, the vertically polarised component has the smallest cloud extinction. An important goal of the study was to derive recommendations for future limb sounding instruments, particularly concerning their polarisation setup. If ice water content is among the retrieval targets (and not just trace gas mixing ratios), then the simulations show that it should be best to observe any of the ±45° and circularly polarised components. These pairs of orthogonal components also make it easier to combine information measured from different positions and with different polarisations.